2016
DOI: 10.1016/j.ccell.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junction Protein 1 Modulates Proteasome Capacity and Proteasome Inhibitor Sensitivity in Multiple Myeloma via EGFR/JAK1/STAT3 Signaling

Abstract: SUMMARY Proteasome inhibitors have revolutionized outcomes in multiple myeloma, but they are used empirically, and primary and secondary resistance are emerging problems. We have identified TJP1 as a determinant of plasma cell proteasome inhibitor susceptibility. TJP1 suppressed expression of the catalytically active immunoproteasome subunits LMP7 and LMP2, decreased proteasome activity, and enhanced proteasome inhibitor sensitivity in vitro and in vivo. This occurred through TJP1-mediated suppression of EGFR/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 37 publications
3
87
0
Order By: Relevance
“…In summary, our finding of noncanonical SQSTM1/p62-Nrf2 pathway activation adds to the growing appreciation from our work and others that carfilzomib resistance in MM can arise via multiple mechanisms [10, 11, 65, 85, 99]. MM is heterogeneous in its etiology and progression so these varied results are not entirely unexpected [100].…”
Section: Discussionmentioning
confidence: 51%
“…In summary, our finding of noncanonical SQSTM1/p62-Nrf2 pathway activation adds to the growing appreciation from our work and others that carfilzomib resistance in MM can arise via multiple mechanisms [10, 11, 65, 85, 99]. MM is heterogeneous in its etiology and progression so these varied results are not entirely unexpected [100].…”
Section: Discussionmentioning
confidence: 51%
“…Finally, the authors of a study published in 2016 127 reported that the expression levels of tight junction protein 1 (ZO-1) are strongly and directly associated with high sensitivity to bortezomib in both myeloma and MCL cell line models and primary myeloma cells 128 . Interestingly, the downstream mechanism implicated in sensitivity was activation of EGFR signaling, which enhanced the levels of proteasome subunit synthesis in a signal transducer and activator of transcription 3 (STAT3)-dependent manner 127 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of clinical relevance, however, such mutations have yet to be detected in clinical samples (13). Additional mechanisms of resistance include alteration of specific cellular pathways such as constitutive activation of NF-κB (14), activation of the chaperone machinery (15,16), or alterations in the EGFR/JAK1/ STAT3 pathway (17).…”
mentioning
confidence: 99%